2017
DOI: 10.1007/s00018-017-2500-6
|View full text |Cite
|
Sign up to set email alerts
|

PTEN proteoforms in biology and disease

Abstract: Proteoforms are specific molecular forms of protein products arising from a single gene that possess different structures and different functions. Therefore, a single gene can produce a large repertoire of proteoforms by means of allelic variations (mutations, indels, SNPs), alternative splicing and other pre-translational mechanisms, post-translational modifications (PTMs), conformational dynamics, and functioning. Resulting proteoforms that have different sizes, alternative splicing patterns, sets of post-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 63 publications
1
56
0
Order By: Relevance
“…Thus, either translocation or retention of GFP-PTEN-L* into the yeast nucleus seems dependent of the presence this poly-Arg stretch. This result is in consonance with evidence reported by Liang et al, who found that the mutation of this sequence eliminated PTEN-M nucleolar localization [38], and with the in-silico prediction of the PTEN-L R6 motif as a nuclear localization sequence [48]. Figure 5C).…”
Section: The Polyarginine Stretch In Pten-l Is Necessary For Nuclear supporting
confidence: 92%
“…Thus, either translocation or retention of GFP-PTEN-L* into the yeast nucleus seems dependent of the presence this poly-Arg stretch. This result is in consonance with evidence reported by Liang et al, who found that the mutation of this sequence eliminated PTEN-M nucleolar localization [38], and with the in-silico prediction of the PTEN-L R6 motif as a nuclear localization sequence [48]. Figure 5C).…”
Section: The Polyarginine Stretch In Pten-l Is Necessary For Nuclear supporting
confidence: 92%
“…Although the exact mechanism of this loss of function is not clear, it is possible that these PTEN mutants have altered nuclear localization patterns, or have impaired E2F1 binding capabilities, which remains to be elucidated. The recent findings of PTEN dimerization [70] and existence of multiple PTEN proteoforms [71] supports the notion that the PTEN mutations in the C2 domain may engage in aberrant PTEN homo/hetero-dimerization, leading to loss of PTEN function. In summary, our transcriptional studies indicate that both PTEN-WT and PTEN-4A can inhibit the transcription of E2F1 regulated genes and that the tumor suppressive effect of PTEN-4A is more pronounced due to its enhanced lipid-phosphatase activity, increased nuclear localization and accessibility of the C2 domain.…”
Section: Discussionmentioning
confidence: 64%
“…Reduced PTEN expression leads to PIP3 accumulation resulting in activation of PI3kinase followed by phosphorylation of AKT. AKT is a pro-cell survival protein that is well documented for its role in HSC proliferation and migration [13,46]. A recent report suggests that PTEN overexpression by adenovirus in the CCl 4 -induced rat liver fibrosis model reduced serum ALT and AST while decreasing collagen deposition in the liver [47].…”
Section: Discussionmentioning
confidence: 99%
“…The phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a dual phosphatase, and its major function is to dephosphorylate phosphatidylinositol 3, 4, 5‑triphosphate (PIP3) to phosphatidylinositol 4, 5‑bisphosphate [13]. Decreased PTEN expression has been reported in fibrotic diseases of the lungs, heart, skin as well as liver [1418].…”
Section: Introductionmentioning
confidence: 99%